2011
DOI: 10.1007/s11661-011-0747-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Delta-Ferrite to Austenite Phase Transformation in a Two-Phase Fe-Al-C Alloy

Abstract: The kinetics of delta-ferrite to austenite phase transformation was investigated using a quenching dilatometer in a Fe-Al-C alloy. The results showed that the austenite phase nucleated along the delta grain boundaries. The transformed austenite morphology changed from cellular to Widmansta¨tten pattern when the holding temperature decreased from 1398 K to 1123 K (1125°C to 850°C). Full partitioning of the substitutional alloying elements was observed and the spacing of the austenite plates was controlled by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In fact, the long‐range atoms diffusion is strongly relative to the phase change process microscopically . Zhou et al found that growth of the austenite front was controlled by the long‐range diffusion of carbon from the center of the delta grains to the growing front in the delta‐ferrite to austenite phase transformation of a Fe–Al–C alloy. Tanimura et al also pointed out that a long‐range diffusion field has a regular atomic and vacancy configuration, diffusion blocking acts as a nonlinear perturbation in the diffusion kinetics and its appearance should substantially influence the temporal evolution of the macroscopic phase state in a diffusion‐controlled phenomenon of Ni–3(Al,V) alloys.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the long‐range atoms diffusion is strongly relative to the phase change process microscopically . Zhou et al found that growth of the austenite front was controlled by the long‐range diffusion of carbon from the center of the delta grains to the growing front in the delta‐ferrite to austenite phase transformation of a Fe–Al–C alloy. Tanimura et al also pointed out that a long‐range diffusion field has a regular atomic and vacancy configuration, diffusion blocking acts as a nonlinear perturbation in the diffusion kinetics and its appearance should substantially influence the temporal evolution of the macroscopic phase state in a diffusion‐controlled phenomenon of Ni–3(Al,V) alloys.…”
Section: Discussionmentioning
confidence: 99%
“…15 In fact, the long-range atom diffusion is strongly relative to the phase change process microscopically. Zhou et al 32 found that growth of the austenite front was controlled by the longrange diffusion of carbon from the center of the delta grains to the growing front in the delta-ferrite to austenite phase transformation of a Fe-Al-C alloy. Tanimura and Koyama 33 also pointed out that a long-range diffusion field has a regular atomic and vacancy configuration, diffusion blocking acts as a nonlinear perturbation in the diffusion kinetics and its appearance should substantially influence the temporal evolution of the macroscopic phase state in a diffusion-controlled phenomenon of Ni-3(Al,V) alloys.…”
Section: Discussionmentioning
confidence: 99%
“…Although the difference is relatively small, it can be clearly seen after amplification. In addition, some pits and bulges were found around the γ phase (position ); Many previous studies proposed that substructures can also provide additional γ phase nucleation sites, enhancing the phase transition kinetics[14,16,17].
Figure 1 Evolution of the γ phase with decreasing temperature.
…”
Section: Resultsmentioning
confidence: 96%